Instantaneous baseline damage localisation using sensor mapping - Salmanpour,MS; Sharif,Khodaei; Aliabadi,MH (IEEE Sensors Journal, 2016)
In this paper an instantaneously recorded baselinemethod is proposed using piezoelectric transducers for damagelocalisation under varying temperature. This method eliminatesneed for baselines required when operating at different temper-atures by mapping a baseline area onto the interrogation area.Instantaneously recorded baselines and current interrogationsignals are calibrated based on the sensor mapping. This allowsextraction of damage scatter signal which is used to localisedamage. The proposed method is used to localise actual impactdamage on a composite plate under varying temperatures. Themethod is also applied to a stiffened fuselage panel to accuratelylocalise impact damage.